Vermi-composting fetches good returns - Singh, B P; Tomar, Manish; Pandey, Rakesh; Singh, Deepa (Indian Farming, 2018)
Mr P. Bajaj further stated that many times the foreign ingredientsin dung hamper the proper conversion process of dung into compost. Gaining experiencing on the basis of learning by doing and on the advisories of KVK’s SMS, he keeps improving his vermicompostunit. Now he is producing the fine quality of vermicompost which hashigh demands among the farmers specifically among the vegetablefarmers and in plant nurseries in Bareilly district. He is receivingsupply order not only from the district of Uttar Pradesh but alsofrom Uttrakhand.